Investigation of the factors affecting students’ self-directed learning readiness in the blended learning model - Bich, Nguyen Thi; Thuy, Kieu Phuong; Mai Huong, Vu Thi; Binh, Pham Thi (Institute of Advanced Engineering and Science, 2025)
Many factors influence the level of readiness for self-directed learning. This study seeks to examine the relationship between learners’ personal characteristics (gender, major, academic year), external factors (facilities, self-study time, peer influence, teacher support), internal factors (cognitive skills, metacognitive skills, attitudes, motivation), and self-directed learning readiness in a blended learning model. The aim is to identify the decisive influencing factors to promote learners’ readiness for self-directed learning and improve blended teaching effectiveness. A survey was conducted with 1,276 students participating in the blended learning model at Hanoi National University of Education in Vietnam. The data were quantitatively analyzed using structural equation modeling with the partial least squares approach in SmartPLS 3, as well as regression analysis in SPSS 20. The findings showed that external factors accounted for 68.7% of the variation in internal factors and 41.6% of the variation in self-directed learning readiness. The study also found that factors such as major and academic year had significant impacts on self-directed learning readiness, as evidenced by statistically significant differences with p-values less than 0.05. These results suggest strategies for educators to effectively address these factors to enhance students’ self-directed learning readiness in blended learning environments.